Evaluation of Cardiopulmonary Stress of the China Clay Mine Workers - Amal Pari; Prakash C. Dhara (Occupational Health and Safety Society of Nepal, 2012)
Background: Several risk factors are associated with cardiopulmonary stress of industrial workers. Most important factors are job strain, job demand, physical effort, work station environment etc. In India, study on occupational cardiopulmonary stress among china clay miners is scanty. Objectives: The present study was aimed to evaluate the cardiopulmonary stresses of the china clay mine workers. Methods: The investigation was carried out on male workers from different china clay mines in the Birbhum district, West Bengal. The cardiovascular stress was evaluated by noting pulse rate of the subjects both during rest and during performance of different types of mine tasks. The cardiovascular stress index (CSI) was evaluated in different mine task. The work rest cycle of different china clay mine tasks was analyzed by video-photographic method. Different pulmonary function parameters, viz, FVC, FEV1, FER and PEF were measured by a digital spirometer to assess the severity of Chronic Obstructive Pulmonary Disease (COPD). Results: The results showed that the working pulse rate and CSI vary with different mine task. It was highest in subjects carrying china clay by head mode. The magnitude of CSI was found to vary with the change of work time and the rest time among the workers. Pulmonary function parameters of china clay mine workers were significantly lower (P<0.01) than other industrial workers. About 79% of total population was suffering from different grades of COPD. Among them, 12% were suffering from severe COPD and 60% from moderate COPD. The higher prevalence of COPD among china clay mine workers might be due to exposure of china clay dust in the work place. Conclusion: It was concluded that the china clay mine workers were suffering from high degree of physiological stress while performing different mine tasks. DOI: http://dx.doi.org/10.3126/ijosh.v2i2.6594 International Journal of Occupational Safety and Health, Vol 2. No 2 (2012) 27-33